Understanding recovery capital: voices of adolescents and caregivers from the Georgia recovery support clubhouse program - Avila Rodriguez, Wendy; Smith, Colleen; Taylor, Brittany J.; McLaren, Susan (Frontiers in Adolescent Medicine, 2025)
BackgroundAdolescents recovering from substance use face developmentally specific challenges requiring tailored supports. Recovery capital (RC), defined as internal and external resources sustaining recovery, offers a framework to address these needs. Guided by the Recovery Capital for Adolescents Model (RCAM), this study explored how adolescents and caregivers experienced RC and investigated perceptions of the Recovery Clubhouse as a context for building and sustaining these resources.MethodsMatched semi-structured interviews were conducted with seven adolescent–caregiver pairs. Adolescents aged 16–18 participated, using guides tailored to age and role. Caregivers completed interviews in either English or Spanish. Interviews were thematically analyzed using RCAM as the guiding framework.ResultsAdolescents and caregivers identified multiple internal and external resources as essential to recovery, often framed in relation to Recovery Clubhouse involvement. Within community recovery capital (CRC), both groups emphasized the value of enjoyable, substance-free activities and creative expression offered through the Clubhouse. In human recovery capital (HRC), adolescents described how intrinsic motivation developed over time, replacing initial external pressures such as court mandates or parental requirements, and noted that Clubhouse participation supported this process. Financial recovery capital (FRC) was also influential: caregivers valued Clubhouse-provided resources for easing financial strain, while adolescents saw employment as a motivator and pathway to independence and long-term goals. Social recovery capital (SRC) revealed the most divergence: adolescents emphasized relationships with Clubhouse staff and friendships outside the program, including peers who used substances. Caregivers viewed these external friendships as risks and instead highlighted the protective role of the Clubhouse's peer network. Interconnections across RC domains were evident, with gains in one area reinforcing others (e.g., CRC participation supporting HRC via coping skills). Additional themes included the importance of family involvement and language-accessible services.DiscussionThe RCAM framework provided a comprehensive lens for understanding recovery resources perceived as valuable by adolescents and caregivers. Findings suggest recovery supports should be developmentally tailored, incorporating engaging activities, opportunities for economic empowerment, staff relationships, and culturally responsive family programming. Recovery Clubhouses were perceived not only as access points for these resources, but also as environments where RC was built and sustained.